2007
DOI: 10.1111/j.1600-0463.2007.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Local collagen‐gentamicin for prevention of sternal wound infections: the LOGIP trial

Abstract: Friberg Ö. Local collagen-gentamicin for prevention of sternal wound infections: the LOGIP trial. APMIS 2007;115:1016-21. In cardiac surgery, sternal wound infection (SWI) continues to be one of the most serious postoperative complications. Coagulase-negative staphylococci (CoNS) have become the most common causative agents of SWI. However, many CoNS species are resistant to routine intravenous antibiotic prophylaxis. 2000 cardiac surgery patients were randomised to routine prophylaxis with intravenous isox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In the Local Gentamicin for Sternal Wound Infection Prophylaxis (LO-GIP) trial (a prospective randomized controlled trial with 2000 procedures), the placement of collagen-gentamicin sponges (with 260 mg gentamicin) within the sternotomy wound prior to closure reduced infection rates from 9% to 4.3%. 15,16 These findings were confirmed with another prospective randomized controlled trial in 2012 showing infection reduction from 3.5% to 0.56%. 39 However, 2 randomized controlled trials in 2005 and 2010 failed to show a significant change in infection with topical antibiotics.…”
Section: 3046supporting
confidence: 76%
See 1 more Smart Citation
“…In the Local Gentamicin for Sternal Wound Infection Prophylaxis (LO-GIP) trial (a prospective randomized controlled trial with 2000 procedures), the placement of collagen-gentamicin sponges (with 260 mg gentamicin) within the sternotomy wound prior to closure reduced infection rates from 9% to 4.3%. 15,16 These findings were confirmed with another prospective randomized controlled trial in 2012 showing infection reduction from 3.5% to 0.56%. 39 However, 2 randomized controlled trials in 2005 and 2010 failed to show a significant change in infection with topical antibiotics.…”
Section: 3046supporting
confidence: 76%
“…Large, prospective, randomized trials have shown that the application of topical gentamicin directly to sternal wounds in cardiac surgery has led to a significant reduction in infection rates. 15,16,39 Similarly, the use of vancomycin powder in posterior spinal fusion for trauma has shown reduced infection rates from as much as 13% to as low as 0%. 17,19 The application of concentrated antibiotics directly to surgical wounds during nonspinal neurosurgical procedures has been more limited.…”
mentioning
confidence: 99%
“…The difference in all groups involving deep SSI was not of statistical significance, except in groups of patients with a BMI>25 kg/m 2 and/or diabetes mellitus [10,12]. On the other hand, there were significantly more reoperations for bleeding in the gentamicin-collagen group (4.0 % vs. 2.3 %).…”
Section: Discussionmentioning
confidence: 79%
“…Most published articles involving topicallyadministered gentamicin with a collagen carrier describe results of the prophylaxis of SSI in a cardiac surgery [5][6][7][8][9][10][11]. Gentamicin-collagen implants of various brand names (Collatamp-G ® , Gentacoll ® , Sulmycin Implant ® ) that contain 130 mg of gentamicin and 280 mg of collagen were put underneath the sternum or between its edges before sternotomy closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation